How Financial Ratios and Firm Size Affect Profitability: Evidence from Food and Beverages Industry in Indonesia - Chesa Ivania Larasati; Purwanto Purwanto (Bina Nusantara University, 2022)
The research was conducted to determine the influence of financial ratios and firm size on the profitability of the company in the food and beverages industry in Indonesia, both partially and simultaneously and to determine which factor has the most significant influence on profitability, from 2014 to 2019. The researcher selected six independent variables to be evaluated using descriptive statistical analysis, classical assumption evaluation, multiple regression analysis, and hypotheses testing with the Microsoft Excel 2016 and EViews 10 as statistical tools. The sampling method and panel data were used to collect the data. There were 72 observation data collected from the Indonesia stock exchange as well as the company's official webpage from 11 food and beverage companies. The financial ratios chosen for the research were working capital to total asset ratio, current ratio, debt to equity ratio, total asset turnover, inventory turnover, and firm size. On the other hand, return on assets was being used as the dependent variable. The research results indicate that, simultaneously, 51,35% influences the profitability of the company. Total asset turnover, inventory turnover, and firm size insignificantly influence the performance of the company, and the debt to equity ratio is the factor with the most significant influence.